Ethics of Information and Communication Technologies - Fabris, Adriano (SpringerBriefs on Ethical and Legal Issues in Biomedicine and Technology,, 2018)
This book discusses key ethical and deontological problems concerning the use of the most common information and communication devices. It focuses on the challenges of the new environments we now find ourselves in thanks to these technologies, and the issues arising from the newly established relationship between the virtual sphere and the real world. Each aspect is analysed by starting from a very specific example or a case study presenting a dilemma that can only be resolved by making a reasoned ethical choice. Rather than thematically addressing only one of the many aspects mentioned above (for example, computer ethics or social network ethics), the book presents a comprehensive introduction to, and a co-ordinated overview of, the various deontological and ethical issues regarding the spread of the most common information and communication technologies. .